Peningkatan Keterampilan Menulis Aksara Jawa Menggunakan Media Audio Visual di Sekolah Dasar - Prabowo, Didik Arif (Universitas Sebelas Maret, 2020)
The purpose of this study was to improve writing skills in Javanese script through audio-visual media for fifth graders at SDN Karangdadap for the 2019/2020 academic year. The subjects of this research are fifth grade teachers and fifth grade students at SDN Karangdadap with a total of 25 students. This type of research is classroom action research (CAR) which consists of two cycles. Each cycle consists of four stages, starting from planning, action, observation and reflection. Data were collected through observation, interviews, and tests. The valid data used are source triangulation and technique triangulation. The data were analyzed using an interactive analysis model consisting of data collection, data collection, and drawing conclusions or levers. The conclusion of this research is that audio-visual media can improve writing skills of Javanese script in fifth grade students of SDN Karangdadap in the 2019/2020 academic year.